PRÁCTICA ÉTICA DEL USO DE LIVE STREAMING COMO HERRAMIENTA PARA LA COBERTURA PERIODÍSTICA EN EL CANTÓN BABAHOYO. - BRIONES HERRERA IRENE MARISOL (2024)
This research focuses on exploring the ethics of digital journalism, specifically the use of Live Streaming as a tool for journalistic coverage in the Babahoyo canton. This technological advancement enables real-time transmission of events to a global audience, radically transforming journalistic practice. However, it faces significant ethical challenges, such as the spread of unverified information, intrusions into privacy, distortions of reality, and the generation of biased content. The study aims to analyze the advantages of an ethical practice in the use of Live Streaming in local journalism, investigating how journalists address ethical dilemmas, adapt traditional norms to the digital context and apply practices to guarantee the quality and veracity of the information transmitted. Through the analysis of local journalistic practices, interviews with professionals in the sector and review of current ethical regulations, it seeks to provide a comprehensive vision of the ethics of Live Streaming in Babahoyo, identifying challenges and opportunities for responsible journalistic practice. The results seek to promote the development of robust digital ethics, promoting responsibility, transparency and veracity in the information disseminated through Live Streaming, as well as the quality of information and the protection of privacy.